Benjamin Disraeli letters:1835-1837 - Disraeli, Benjamin (Letters of Benjamin Disraeli., 1982)
The 334 letters in this volume cover the period from Disraeli's establishment in the Tory camp under the patronage of Lord Lyndhurst to his election to parliament in 1837. The most important issue to which they speak is the course of Disraeli's political ambitions.